Sravnitel'naja ocenka effektivnosti sredstv i metodov terapii funkcional'noj venoznoj nedostatocnosti nižnich konecnostej u vysokokvalificirovannych sportsmenov - Safonov, L. V.; Rostovtsev, V. L.; Kozlovsky, A. P.; Shurygin, S. N.; Pankov, V. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In the article the actual problem of therapy of functional disturbance of venous blood circulation of the lower limbs that occurs in elite athletes of speed-power and cyclic sports under the influence of intensive physical exertion is considered. The lack of a specific clinical picture and subjective manifestations similar to manifestations of fatigue, functional disorders of venous circulation of extremities in elite athletes often not diagnosed in the process of medical examination and, accordingly, remainwithout specific prevention and therapy. The article is devoted to the evaluation of the effectiveness of modern means and methods of therapy of functional venous insufficiency of the lower limbs in highly qualified athletes of various sports and gives recommendations for the development of effective programs for the therapy of functional disorders of the venous blood circulation of the lower extremities in elite athletes.